2003
DOI: 10.1096/fj.03-0292fje
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces growth inhibition and apoptosis in metastatic breast cancer cells via de novo ceramide signaling

Abstract: Resveratrol (3,4',5-trans-trihydroxystilbene), a phytoalexin present in grapes and red wine, is emerging as a natural compound with potential anticancer properties. Here we show that resveratrol can induce growth inhibition and apoptosis in MDA-MB-231, a highly invasive and metastatic breast cancer cell line, in concomitance with a dramatic endogenous increase of growth inhibitory/proapoptotic ceramide. We found that accumulation of ceramide derives from both de novo ceramide synthesis and sphingomyelin hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 42 publications
4
103
0
1
Order By: Relevance
“…Resveratrol has been reported to induce caspase activation subsequent to mitochondrial release of cytochrome c (2,4,21), caspase activation independent of cytochrome c release (25), caspase-8-mediated Bax/Bak-dependent cell death (28), p53-or Bax-dependent and -independent cell death (26), ceramide-mediated cell cycle arrest and apoptosis (42), and death receptor (CD95)-dependent death signaling (38). Multiple and diverging death signaling events, all converging to apoptosis in different cells, suggest that resveratrol-induced cell death varies from cell to cell, indicating a possible role for regulatory molecules of apoptosis that govern the apoptotic threshold of a cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol has been reported to induce caspase activation subsequent to mitochondrial release of cytochrome c (2,4,21), caspase activation independent of cytochrome c release (25), caspase-8-mediated Bax/Bak-dependent cell death (28), p53-or Bax-dependent and -independent cell death (26), ceramide-mediated cell cycle arrest and apoptosis (42), and death receptor (CD95)-dependent death signaling (38). Multiple and diverging death signaling events, all converging to apoptosis in different cells, suggest that resveratrol-induced cell death varies from cell to cell, indicating a possible role for regulatory molecules of apoptosis that govern the apoptotic threshold of a cell.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide, etoposide, and other genotoxic agents are known to be the inducers of caspase-2 (52). Ceramide generation with resveratrol reported in MADA-MB-231 breast cancer cells may also be a possible trigger for caspase-2 activation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of human mammary epithelial cells with C 2 -ceramide increases levels of COX-2 protein and mRNA and enhances prostaglandin E 2 synthesis (42). Recently, other studies have shown that resveratrol induces apoptosis through a ceramide signal transduction pathway (43,44). It is therefore reasonable to speculate that the induction by resveratrol of COX-2 -dependent apoptosis requires ceramide signaling.…”
Section: B Mcf-7 Cells Were Treated With 10mentioning
confidence: 97%
“…Many cancer chemotherapies and radiation are potent inducers of autophagy. 5 Resveratrol (Res), a polyphenol found in grapes, peanuts and other plants, has potent antioxidant and antitumorigenic activities, 6 affects tumor initiation and promotion, and arrests angiogenesis and metastasis. It is also able to stimulate apoptosis, arrest cell cycle and suppress kinase pathways.…”
mentioning
confidence: 99%